El graffiti en metálico: análisis sobre el graffiti y la circulación monetaria - Figueroa-saavedra, Fernando (Historia y Comunicación Social, 2007)
The graffiti makers have used of coins and banknotes like a writing supports along the History and in the modern times particularly. The aware of symbolic value, the practical use like private media or the intervention in the monetary traffic are some factors that have become the currency graffiti in a feature of the contemporary graffiti. Its rooting and proliferation are showed through the examples, located in the 19th, 20th, and 21st centuries in Europe and America.